Crime and Punishment- An Economic Analysis of Illegal fishing - Coelho, M.; Filipe, J. A.; Ferreira, M. A. M. (Anales de Economia Aplicada-Anais de Economia Aplicada, 2009)
Public enforcement of law is an obvious important theoretical and empirical subject for Social Sciences. First literarture dates from eighteenth century: Montesquieu, Beccaria and Bentham. After the sophisticated analysis of Bentham, enforcement subject "lay essentially dormant in economic scholarship", until BeCKER (1968) article, "Crime and Punishment: An Economic Approach". In Fisheries Economics, this can be seen as an externality arising when exclusive propery rights are absent, and that absence depends, particularly, on the costs of defining and enforcing exclusivity. Efficiency considerations don't dictate, only by themselves, the choice of a certain property rights regime. In "common property" the re-alignment of the property rights can have a very high or even prohibitive cost. This model combines standard Economics of Fisheries Analysis (Gordon/Scharfer model) with Becker´s Theory of "Crime and Punishment". The conclusions are used to study the design and reform of the control and monitoring regime of the Common Fisheries Policy.